Effectiveness of inspectors' team in increasing compliance with personal protective equipment use and reducing COVID19 infection spread among healthcare workers - Mohammad Shehab; Sameera Shuaibi; Iman Qadhi; Ahmad Alfadhli (Elsevier, 2021)
Background: Healthcare workers (HCW) were amongst the front-liners in the mission to tackle the COVID-19 pandemic and thus bore a huge risk of infection. Therefore, personal protective equipment (PPE) is of vital importance. There are several methods described in the literature to increase compliance with PPE use and reduce occupational infections. One of those methods is the institution of PPE inspectors that ensure proper adherence to PPE protocols and ultimately improve the outcomes of many HCWs. Methods: A team of PPE inspectors was introduced in a tertiary care university hospital, where they randomly evaluated and reinforced PPE use in accordance with the guidelines set by the local health authority. The study period was from the 10th of May 2020 until the 31st of August 2020. The evaluations were divided into three categories; appropriate, missing, or unnecessary use of PPE and were compared to trends in healthcare workers' COVID-19 infection rates. Results: A total of 720 HCWs were evaluated from the 10th of May 2020 until the 31st of August 2020. The appropriate use of PPE increased from 56% to 89% during the study period. Meanwhile, the incidence of COVID-19 infection among HCWs, which has peaked to 31 cases per day on the 18th of May 2020, has been declining to below 5 cases per day towards the end of the study period. Conclusion: PPE inspectors' team served a positive role in increasing compliance with PPE use and was associated with a reduction in the transmission of SARS-Cov-2 among HCWs.